Pengaruh Pendekatan Realistic Mathematics Education Berbasis Media Tangga Pintar Terhadap Hasil Belajar Matematika Pada Siswa SD - Dewi Yulianasari; Misdalina Misdalina; Tanzimah Tanzimah (Journal on Education, 2023)
This study aims to determine the effect of the smart ladder-based Realistic Mathematics Education approach on mathematics learning outcomes in elementary school students. This research uses an experimental method, namely True Experiment Design. With the form of Posttest-Only Control Design.The sample in this study of grade 1B and 1C students totaling 40 students, Simple Random Sampling technique was taken. Based on the hypothesis test conducted by this researcher using the t-test of two free samples (Independent sample t-test) obtained tcount results of 4,591 and ttable value = 1.686 with α=0.05 and df= 38, then tcalculate ≥ ttable so that HO is rejected. From the hypothesis test data, it can be concluded that there is an influence in the smart ladder-based Realistic Mathematics Education approach on mathematics learning outcomes in elementary school students.